Stages and duration of the seminiferous epithelium cycle in the bat Sturnira lilium - Morais, Danielle B.; Paula, Tarcízio A. R.; Barros, Mirlaine S.; Balarini, Maytê K.; Freitas, Mariella B. D.; Matta, Sérgio L. P. (Journal of anatomy, 2013)
Knowledge of the stages that compose the seminiferous epithelium cycle (SEC) and determination of the duration of spermatogenic processes are fundamental for the accurate quantification of the dynamics of spermatogenesis. The aim of this study was to characterize the stages that compose the SEC of the bat Sturnira lilium, including evaluation of the average frequency of each of these stages throughout the year and calculation of the duration of the spermatogenic process. An ultrastructural characterization of the formation of the acrosomal cap was also performed. Testicular fragments were processed for morphological and immunohistochemical analysis as well as ultrastructural analysis using transmission electron microscopy. According to the tubular morphology method, the SEC in S. lilium is divided into eight stages, following the pattern found in other mammals. Primary spermatocytes were found at zygotene in stage 1 of the cycle. There was no variation in frequency of each of the stages over the seasons, with stage 1 being the most frequent, and stage 7 the least frequent. The duration of one seminiferous epithelium cycle was 3.45 days, and approximately 15.52 days were required for the development of sperm from spermatogonia. Ultrastructural characterization allowed the formation of the acrosomal cap in round spermatids to be monitored. In conclusion, the stages that compose the SEC in S. lilium are generally similar to those described for other mammals, but the duration of the spermatogenic process is shorter than previously recorded for mammals. The presence of primary spermatocytes at zygotene in stage 1 of the cycle is probably due to the longer duration of this stage.